Critical discourse analysis in transcultural spaces - Downes, Lynn; Kim, Marcia (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2019)
Critical Discourse Analysis (CDA) is an analytical framework developed for studying power and inequalities as manifested in language in contemporary capitalist society (Fairclough, 2010). CDA examines evidence of unequal power relations in discursive events (Fairclough, 2003)and shows the role of discourse in constructing the social world, social identities and influences in social change (Fairclough, 1992). “Critical” suggests that power struggles exist in society, so CDA aims to expose ideological features of discourse (Fairclough, 2010, p. 4). This article provides a brief overview of CDA and discusses its specific characteristics in relation to the authors’ doctoral research. The first author is applying CDA to an examination of language change, specifically in regard to taboo language and swearing at secondary schools and the second author is using CDA in an exploration of soft skills in workplace communication. The article also examines the personal reflections of the authors on how the emerging transcultural experience in Brisbane, Australia, on the 2017 International Doctoral Seminar and Conference has benefited their individual journeys, their knowledge of CDA as well as their prospective research.